Obesity Risk Factors among 25-65 Years Old Adults in Bogor City, Indonesia: A Prospective Cohort Study - Sudikno, Sudikno; Syarief, Hidayat; Dwiriani, Cesilia Meti; Riyadi, Hadi; Pradono, Julianti (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2018)
This research was aimed to identify the obesity risk factors in adults aged 25-65 years old in 2011-2014. The study used secondary data from “Cohort study on risk factors of non-communicable diseases” that was collected for two years in 2011-2013 and 2012-2014. The research was designed as a prospective cohort study. The number of subjects was 1006, consisted of 364 men and 642 women. Results showed a 25% prevalence of obese (BMI≥25 kg/m2). Multivariate Cox regression analysis showed the risk factors of obesity in adults aged 25-65 years old were gender, smoking habit, consumption of fatty foods, and duration of smoking habit. During the two years of observation, obesity developed faster in female subjects compared to male subjects, after adjusted to smoking habit, fat intake, and interaction between smoking habit and time. The risk of obesity in adults can be reduced by not starting smoking at early age and reducing consumption of fatty foods.